Issues and Challenges of Buroq Oil Companies in Malaysia - Rali, Mohd Nor (2023)
This study investigates the sustainability aspects of rural petrol station retailing, focusing on the specific case of Buraq Oil Petrol Station and Service. With growing concerns about environmental impacts and changing market dynamics, the study examines how this rural petrol station navigates challenges and harnesses opportunities to ensure long-term sustainability. Through a comprehensive analysis of operational strategies, community engagement, and environmental practices, this research contributes to the understanding of sustainable practices in the context of rural petrol station retailing, offering insights for both the industry and local communities. The aim of this study is to determine the most suitable approach to ensure the sustainability and long-term viability of these stations in rural settings. The research objectives include analyzing the challenges faced by Buraq Oil Petrol Station and Services, evaluating the feasibility and effectiveness of establishing large oil and gas stations, and recommending strategies for improving the sustainability of oil and gas stations in rural areas. The study employs a qualitative research approach to gather data through surveys, interviews, and case studies. The findings of this research will provide valuable insights into the optimal and sustainable solutions for oil and gas stations in rural areas, facilitating informed decision-making for stakeholders, policymakers, and industry professionals. The study's outcomes have the potential to contribute to the development of more sustainable practices in the petroleum industry, particularly in rural regions, promoting economic growth and environmental stewardship.